Dangerous Liaisons in Cairo: Reginald Q. Henriques and the Taylor-Schechter Genizah Manuscript Collection - Jefferson, Rebecca (Judaica Librarianship, 2017)
When Solomon Schechter published his opus magnum, the co-edited volume of The Wisdom of Ben Sira, in 1899, he took the trouble to express his gratitude towards one Reginald Q. Henriques for his help in the past and still ongoing. This article attempts to answer the question: who was this Mr. Henriques and what was the nature of his connection to Schechter? Using previously unpublished archival evidence, this question is explored in depth, as well as the question of why Schechter chose to acknowledge this individual precisely at that point. It also provides an in-depth account, together with transcriptions of original letters, of the activities of the various genizah manuscript collectors operating in Cairo during the late 1890s and the unspoken race to recover the original Hebrew version of the Book of Ben Sira. These activities are viewed against the backdrop of an all-pervasive scholarly culture that was critical of post-biblical Judaism, as well as prevailing Cairene attitudes and behaviors towards those engaged in the recovery and export of antiquities, and the varying (often arbitrary) authorizations and restrictions exercised by Cairo's European and Egyptian administrators. Finally, it takes a closer look at the contents of today's Taylor-Schechter Genizah Collection at Cambridge University Library in an attempt to discover greater details about its exact provenance.